(untitled) (Al-Qamar, 2025)
The use of human body parts in medicine and cosmetics raises profound scientific, ethical, religious, and legal questions. This study employs a multidisciplinary approach to examine these practices through the lens of Islamic jurisprudence, biomedical evidence, and global regulatory frameworks. Qur’anic texts, Hadith, and rulings from the four Sunni schools of thought are analyzed to clarify Islamic perspectives on the sanctity of the human body. A scientific and ethical review evaluates the therapeutic benefits of transplantation and regenerative medicine alongside the contested use of human-derived materials in cosmetics. Case studies from Islamic countries explore how legal systems integrate religious rulings with contemporary biomedical regulations. Data collection combines content analysis of jurisprudential texts, contemporary fatwas, and scientific literature, supported by expert interviews with scholars, legal specialists, and medical professionals. The findings are presented from social, religious, economic, and industrial perspectives, offering a balanced and culturally sensitive framework for policymaking. By integrating jurisprudential traditions with modern scientific and ethical debates, this study provides evidence-based insights to guide the responsible and ethical use of human body parts in both medical and cosmetic applications.